2002
DOI: 10.2106/00004623-200208000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Predictors of Scoliosis in Patients with Myelomeningocele

Abstract: Structural changes in the forefoot of individuals with diabetes and a prior plantar ulcer." The Journal of Bone and Joint Surgery.84,8. 1395. (2002 Background: Plantar ulcers produced by diabetic foot disease are devastating and costly. Better understanding of the ulcer-producing process is important to improve detection of feet that are at risk and to improve intervention. We identified and quantified soft-tissue and osseous structural changes in the forefoot of diabetic patients with a prior plantar ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 59 publications
0
45
0
1
Order By: Relevance
“…In a study done by Trivedi et al in Connecticut, USA it was found that the prevalence of scoliosis among myelomeningocele patients was as high as 80-90%. 18 In this study 10.6% of the school children who were delivered pre-term and 3.2% of those who were delivered at full term of pregnancy had positive scoliosis findings. It was found that the maturity of foetus during delivery had a highly significant (p <0.001) association with positive scoliosis findings with preterm infants at 3.6 times greater risk of scoliosis than full term ones (95% CI -1.34-9.89).…”
Section: Scoliometer Device and Scoliometer Appmentioning
confidence: 50%
“…In a study done by Trivedi et al in Connecticut, USA it was found that the prevalence of scoliosis among myelomeningocele patients was as high as 80-90%. 18 In this study 10.6% of the school children who were delivered pre-term and 3.2% of those who were delivered at full term of pregnancy had positive scoliosis findings. It was found that the maturity of foetus during delivery had a highly significant (p <0.001) association with positive scoliosis findings with preterm infants at 3.6 times greater risk of scoliosis than full term ones (95% CI -1.34-9.89).…”
Section: Scoliometer Device and Scoliometer Appmentioning
confidence: 50%
“…Helpful definitions for the incidence and prevalence of scoliosis in children with myelomeningocele have been developed by Trivedi et al (29)(28). In their survey, a patient population with a Cobb angle of more than 20 degrees was determined as cases with scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the spinal curvatures develop during early stages of life, while nearly 40% of them occur after age 9. A small proportion is seen after age 15 (29). Scoliosis in patients with myelomeningocele can develop secondary to congenital, idiopathic, or spinal dysraphism.…”
Section: Discussionmentioning
confidence: 99%
“…Hip problems restricting the ambulatory capacity of the patient mostly occur as a result of instability together with varying degrees of muscle contractures causing pelvic obliquity and scoliosis [17]. Pelvic ring muscles do not function properly in patients with upper-level lesions and thus reduction of the hip generally ends up with high failure rates in such patients.…”
Section: Introductionmentioning
confidence: 99%